Czy nacjonalizm może być wartością? O "nacjonalizmie" w słownikach i współczesnej publicystyce = Can nationalism be a value? "Nationalism" in Polish dictionaries and contemporary journalism - Polkowska, Laura (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This sketch is devoted to the concept of nationalism and its semantic profiling in dictionaries and contemporary Polish journalism. In lexicographic definitions, "nationalism" is treated as a neutral or negatively marked term. Only one - a political dictionary from the twenties of the twentieth century - treats it as a positively marked concept. However its author was an activist from the National Democratic Party.
Keywords: nacjonalizm; profilowanie; semantyka; wartość; leksykografia; publicystyka; nationalism; linguistic profiling; semantic; values; lexicography; weekly